The Recurrence Rates at Three Years for the Conservatively Managed UTUC Cases Using NBI-Assisted Flexible Ureteroscopy and Holmium Laser Vaporization - Petrisor Geavlete; Valentin Iordache; Razvan Multescu; Alexandra Paunescu; Cosmin Ene; Razvan Popescu; Catalin Bulai; Bogdan Geavlete (Medicina)
Background and Objectives: This study aimed to evaluate the recurrence rates at three years for upper tract urothelial carcinoma (UTUC) cases managed conservatively, using Narrow Band Imaging (NBI)-assisted flexible ureteroscopy and Holmium laser vaporization. Materials and Methods: The study group included 61 patients who were diagnosed with NBI-assisted visualization with superficial pyelo-calyceal urothelial tumor lesions, treated conservatively by the flexible ureteroscopic approach and Holmium laser vaporization, also assisted by NBI. This was compared with a control group with the same number of cases, which underwent the same procedure, but without NBI technology. Recurrence rates, the rate of patients who underwent nephroureterectomy, and cancer-specific survival were compared. Results: The relapse rate at 1 year was 3.3% in the study group, and respectively 8.2% in the control group (p < 0.05). Depending on the histological characteristics, at 1 year the relapse rates in the study group were 1.8% in patients with low-grade tumors and 20% in those with high-grade tumors. At 3 years, the relapse rate was 11.5% in the study group versus 18% in the control group, (p < 0.05): 7.1% in patients with low-grade lesions and 40% in patients with high-grade lesions versus 21.4% in patients with low-grade lesions and 100% in patients with high-grade lesions (both arms with statistically significant differences, p < 0.05). Cancer-specific survival was 93.4% in the study group versus 86.9% in the control group (p < 0.05). Conclusions: The recurrence rates at three years for the UTUC cases managed conservatively, using NBI-assisted flexible ureteroscopy and Holmium laser vaporization, were lower than in patients treated by the same technique without NBI assistance, both in low- and high-grade tumors. Cancer-specific survival was also significantly improved by the association of NBI visualization during diagnosis and laser vaporization.